Thank you for registering.

One of our academic counsellors will contact you within 1 working day.

Click to Chat

1800-5470-145

+91 7353221155

CART 0

• 0
MY CART (5)

Use Coupon: CART20 and get 20% off on all online Study Material

ITEM
DETAILS
MRP
DISCOUNT
FINAL PRICE
Total Price: Rs.

There are no items in this cart.
Continue Shopping

10 years ago

Hello Mohit

Question : 2

x.root(1+y) + y.root(1+x) = 0

x / root(1+x) = -y/root(1+y)

square both side

x^2/(1+x) = y^2/(1+y)

x^2 + x^2.y = y^2 + x.y^2

x^2 - y^2 = xy^2 - x^2y

(x-y)(x+y) = xy(y-x)

so  x + y = -xy

or  x + y + xy = 0

y(1+x) =- x

y = -x/(1+x)

dy/dx = -1/(1+x)^2  ans

--------------------------------------------------------------------------------------------------------------------------------------

rajan jha
49 Points
10 years ago
let x=sinb & y=sint then put it in the question. u got cosb + cost = a(sinb-sint) =)2cos(b+t/2).cos(b-t/2)=a(2cos(b+t/2).sin(b-t/2)) =)cos(b-t/2)=asin(b-t/2) (after cancelling 2cos(b+t/2) both sides) =)cot(b-t/2)=a =)b-t=2cot-1(a) (here -1 denotes inverse) =)sin-1(x)-sin-1(y)=2cot-1(a) differentiating both sides, and get the r.h.s as zero as it is constant next step the answer comes like my answer?